Field-based physiological testing of wheelchair athletes - Goosey-Tolfrey, V. L.; Leicht, C. A. (Sports Medicine, 2013)
The volume of literature on field-based physiological testing of wheelchair sports, such as basketball, rugby and tennis, is considerably smaller when compared with that available for individuals and team athletes in able-bodied (AB) sports. In analogy to the AB literature, it is recognized that performance in wheelchair sports not only relies on fitness, but also sport-specific skills, experience and technical proficiency. However, in contrast to AB sports, two major components contribute towards `wheeled sports` performance, which are the athlete and the wheelchair. It is the interaction of these two that enable wheelchair propulsion and the sporting movements required within a given sport. Like any other athlete, participants of wheelchair sports are looking for efficient ways to train and/or analyse their technique and fitness to improve their performance. Consequently, laboratory and/or field-based physiological monitoring tools used at regular intervals at key time points throughout the year must be considered to help with training evaluation. The present review examines methods available in the literature to assess wheelchair sports fitness in a field-based environment, with special attention on outcome variables, validity and reliability issues, and non-physiological influences on performance. It also lays out the context of field-based testing by providing details about the Paralympic court sports and the impacts of a disability on sporting performance. Due to the limited availability of specialized equipment for testing wheelchair-dependent participants in the laboratory, the adoption of field-based testing has become the preferred option by team coaches of wheelchair athletes. An obvious advantage of field-based testing is that large groups of athletes can be tested in less time. Furthermore, athletes are tested in their natural environment (using their normal sports wheelchair set-up and floor surface), potentially making the results of such testing more relevant than laboratory testing. However, given that many tests, such as the multistage fitness test and the Yo-Yo intermittent test, have originally been developed for AB games players, the assumption that these can also be used for wheelchair athletes may be erroneous. With the array of AB aerobic and anaerobic field tests available, it is difficult to ascertain which ones may be best suited for wheelchair athletes. Therefore, new, wheelchair sport-specific tests have been proposed and validated. Careful selection of tests to enable coaches to distinguish between disability classifications, wheelchair proficiency and actual performance improvements is paramount as this will not only enhance the value of field-based testing, but also help with the development of meaningful normative data.